Interaction between "Accelerating-Packing" Flows for the Bryan-Pidduck Model - Gukalov, A.A. (Журнал математической физики, анализа, геометрии, 2013)
The interaction between the "accelerating-packing" flows in a gas of rough spheres is studied. A bimodal distribution with the Maxwellian modes of special forms is used. Different sufficient conditions for the minimization of the uniform-integral error between the sides of the Bryan-Pidduk equation are obtained. Исследовано взаимодействие двух "ускоряющихся-уплотняющихся" потоков в газе из шероховатых сфер. Использовано бимодальное распределение с максвелловскими модами специального вида. Получены различные условия, достаточные для минимизации равномерно-интегральной невязки между частями уравнения Бриана-Пиддака.